Scenarios of profitability of western Mediterranean demersal fisheries in an effort control regime. (15th December 2021) - Akbari, Negar; Maynou, Francesc; Bjørndal, Trond; Failler, Pierre; Drakeford, Benjamin; Forse, Andy
Abstract: In 2019 a multiannual plan for Mediterranean demersal fisheries came into force with the objective to reduce the overexploitation of fisheries in the region by implementing effort control regimes. These measures, however, have the potential to adversely impact the local employment and profitability of the fisheries. In this paper, we examine scenarios on the short term and long term levels of economic yield of the sector using the two main drivers of fuel price and employment. Three main scenarios are defined as i) maintaining the average status quo, ii) effort control regimes implemented in the 2019 multiannual plan, and iii) flexible effort control regimes. For each of the aforementioned scenarios, three main fleets and five main conditions are considered, and the results will be compared and contrasted. The results in this paper show that the future rise in fuel price, which is anticipated due to global efforts to reduce emissions, along with the current effort reduction strategies could significantly threaten the sustainable profitability of the sector, and policy measures that could balance this issue should be implemented. Policy interventions and investments should be directed at technological advancements such as modernisation and increasing efficiency of fleet to reduce fuel use, utilisation of highly efficient gear technologies, shortened trips to fishing grounds, and increase in value creation in other parts of the fisheries supply chain to mitigate the serious challenges in terms of local employment and profitability facing the Mediterranean fisheries. Highlights: The profitability of NW Mediterranean fisheries is assessed considering the effort control regime implemented in 2019. Results show that the long term economic performance, could be severely affected in the effort control regime . Policy recommendations include modernisation of fleet, improved marketing strategies, and diversification.